THE STUDY OF CUSTOM-FITTED FEMORAL COMPONENT KNEE IMPLANT FOR HIGH FLEXION - FUA-NIZAN, ROSDAYANTI (2020)
Knee joint consists of bones and cartilages to facilitate movements. Osteoarthritis damages the joint, leading to Total Knee Replacement with knee implant components. Knee implants are manufactured and designed by European and Western manufacturers to suit Caucasian’s anatomy and flexion needs, which limits the sizes for Asian anatomy and higher flexion needs. This research hypothesizes that modified femoral component will improve the fit and feasibility for high flexion. Thus, the objectives for this research are to process, reconstruct, and modify Magnetic Resonance Imaging (MRI) images into femoral component, to analyse the stress distribution and strain of the modified femoral component and formulate correlation between stress distribution and strain to the flexion angle, and to analyse the dimensional distinction in between the modified femoral component with existing femoral component knee implant.